Gestión de operaciones turísticas para el desarrollo económico del cantón Quevedo, año 2019 - Silva Aviles, Tyrone Alexis (2019)
The present work called "Management of tourism operations for the economic development of the Quevedo canton, year 2019" is based on the little interest that is placed on this sector of the economy, being one of the most important in promoting the economic development of the country. Quevedo being the provincial economic center and a mandatory crossing point to address the different parts of the Ecuadorian territory, in addition to having attractions that being exploited in a responsible manner would positively contribute to the economic growth of the same, this has not occurred, which It makes us realize that there is very little interest from the main actors in the tourism sector to help boost tourism in the canton. For the development of the research an explanatory type of research was used to try to determine the causes and consequences of the current situation of the tourist operations, the descriptive research to give an explanation as complete as possible of the subject and the quantitative research to make a study of reality through the techniques of data collection such as interview and survey which would help us to reach conclusions and final recommendations.